Pengaruh Keputusan Pendanaan, Kebijakan Deviden dan Keputusan Investasi terhadp Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di BEI pada Tahun 2015-2019: Studi Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar - Mutia Sari, Meli; Gendro Wiyono; Maulida, Alfiatul (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study was to determine the effect of the independent variables, namely funding decisions, devidend policies, invesmenst decisions on the dependent variable namely frim value. This research is a descriptive statistical study with the population used is a manufacturing company in the food and beverage sub-sector that has been listed on the indonesia stock exchange in the 2015-2019 period. The sample was determined using the purposive sampling method from 55 total samples in the 2015-2019 period, only 11 companies that met the criteria. The type of data used is secondary data from the sample company’s financial statements. This research uses multiple linear regression analysis method.The results of this study indicate that funding decisions have a positive effect on frim value, dividend policy has a negatif effect on frim value and investment dcisions have a positive effect on frim vakue.